Problematika Penyidikan Korupsi Pembangunan Jaringan Transmisi Air Baku Di Kabupaten Bone Bolango - Suardi Rais; Rusmulyadi Rusmulyadi; Saharuddin Saharuddin (ILIN Institute, 2021)
This study aims to analyze the role of prosecutors' investigators in uncovering corruption cases, as well as to find out the factors that hinder Gorontalo High Prosecutor's investigators in uncovering corruption cases in the raw water supply project in Bone Bolango Regency. The research method used is empirical legal research or non-doctrinal research, which is a type of legal research that looks at law from a perspective outside of legal science. The results of this study indicate that: (1) the role of the prosecutor in the most basic criminal field is to conduct investigations into special crimes and carry out prosecutions. The Gorontalo High Prosecutor's Office, after receiving information about an alleged corruption case, formed an intelligence team of inspectors to seek initial information in finding allegations of corruption, as well as coordinating with related parties, presenting technical experts to assess the procurement of goods used in the project. If there is a loss to the state, the high attorney will then issue an investigation order and make an investigation plan. (2) In carrying out investigations into criminal acts of corruption in the procurement of raw water in Bone Bolango Regency, there are two things that become obstacles to the Gorontalo High Court, namely the slow results of examinations from technical experts and the slow results of audits from BPKP. Penelitian ini bertujuan menganalisis peranan penyidik kejaksaan dalam mengungkap kasus korupsi, serta mengetahui faktor apa yang menjadi hambatan penyidik Kejaksaan Tinggi Gorontalo dalam mengungkap tindak pidana korupsi pada proyek pengadaan air baku di Kabupaten Bone Bolango. Metode penelitian yang digunakan adalah Penelitian hukum emperis atau penelitian non-doktrinal adalah tipe penelitian hukum yang melihat hukum dari sudut pandang diluar ilmu hukum. Hasil penelitian ini menunjukkan bahwa: (1) peran kejaksaan dalam bidang pidana yang paling mendasar adalah melakukan penyidikan terhadap tindak pidana khusus dan melakukan penuntutan. Kejaksaan Tinggi Gorontalo setelah mendapat informasi adanya dugaan tindak pidana korupsi membentuk tim intelejen pemeriksa untuk mencari informasi awal dalam menemukan adanya dugaan tindak pidana korupsi, serta melakukan koordinasi dengan pihak terkait, menghadirkan ahli teknis untuk menilai pengadaan barang yang digunakan dalam proyek tersebut. Jika terdapat kerugian negara kejaksaan tinggi kemudian mengeluarkan surat perintah penyidikan dan membuat rencana penyidikan. (2) Dalam pelaksaan penyidikan tindak pidana korupsi pada pengadaan air baku di Kabupaten Bone Bolango terdapat dua hal yang menjadi hambatan Kejaksaan Tinggi Gorontalo yaitu lambatnya hasil pemeriksaan dari ahli teknis dan Lambatnya hasil audit dari BPKP.